Developing A Tax Morale Framework for Malaysian Online Businesses: Towards Revenue Sustainability - Ibrahim, Idawati; Mansor, Muzainah; Saad, Natrah; Mat Udin, Noraza (UUM, 2021)
In achieving the goal of becoming a high-income nation by 2020, the Malaysian government has promoted and subsidised the e-commerce activities. The e-commerce businesses in Malaysia generate billions of ringgit annually. However, it was reported that they do not pay tax due to the absence of a tax structure for this kind of business. It will be a revenue loss for the government if nothing is done about it because going forward, more businesses will go into digital economy. Hence, this research proposes that high level of tax morale among online businesses can help to increase voluntary tax compliance among them. This justifies the fundamental necessity of this research in developing a tax morale framework for Malaysian online businesses in order to move towards tax revenue sustainability in the long run. The objectives of this study are threefold, 1) To reveal the nature of socio-economic of online businesses, 2) To unveil the level of tax morale of online businesses, and 3) To generate a tax morale framework for online businesses. This research proposes to examine the issue from a qualitative paradigm. The study proposes to use qualitative design because it allows data to be collected in the field at the site where participants experience the issue under study. Qualitative research enables researchers to gather up-close information by talking directly to people under study and seeing them behave and act within their context. This condition is very important especially in studying the internal values such as the tax morale of the respondents. The study will have significant impacts on the society, economy, and nation as a whole as the framework may improve voluntary compliance among the online business taxpayers, improve the efficiency of the tax authority in Malaysia, and improve tax revenue sustainability in order to achieve the government’s goal to become a high-income nation by 2020.